Sequence and structural elements that contribute to efficient encephalomyocarditis virus RNA translation. - Duke, G M (1992)
The nucleotide sequence of the 5' nontranslated region of encephalomyocarditis virus (EMCV-Rueckert) was determined, and a consensus RNA structural model for this sequence (850 bases) and three other poly(C)-containing cardioviruses (mengovirus, EMCV-B, and EMCV-D) was created through reiterative use of a minimum-free-energy folding algorithm. The RNA elements within this region which contribute to translation of EMCV proteins were mapped in cell-free reactions programmed with cDNA-derived RNA transcripts. The data provide evidence that stem-loop motifs I, J and K, formed by viral bases 451 to 785, are important components of cap-independent translation. In contrast to other reports, a minimal role for stem-loop H (bases 406 to 444) in translational activity is indicated. Small 5' nontranslated region fragments (bases 667 to 797) containing the J and K motifs proved strong competitive inhibitors when added to cell-free reactions programmed with exogenous capped or uncapped mRNAs. The putative sequestering of required translational factors by this segment clearly contributes to translational activity, but also suggests a possible competitive mechanism for the down regulation of host protein synthesis during viral infection.